Zein-Based Nanocarriers: Advances in Oral Drug Delivery - Yuxin Liu; Dongyu An; Xiangjian Meng; Shiming Deng; Guijin Liu (Pharmaceutics)
Oral administration remains the preferred drug delivery route but faces formidable gastrointestinal barriers, including enzymatic degradation, solubility limitations, and poor epithelial absorption. Zein-based nanocarriers (ZBNs), derived from maize prolamin, provide a transformative platform to address these challenges. This review synthesizes recent advances in ZBNs’ design, highlighting their intrinsic advantages: structural stability across pH gradients, self-assembly versatility, and a surface functionalization capacity. Critically, we detail how engineered ZBNs overcome key barriers, such as enzymatic/chemical protection via hydrophobic encapsulation, the enhanced mucus penetration or adhesion through surface engineering, and improved epithelial transport via ligand conjugation. Applications demonstrate their efficacy in stabilizing labile therapeutics, enhancing the solubility of BCS Class II/IV drugs, enabling pH-responsive release, and significantly boosting oral bioavailability. Remaining challenges in scalability and translational predictability warrant future efforts toward multifunctional systems, bio-interfacial modeling, and continuous manufacturing. This work positions ZBNs as a potential platform for the oral delivery of BCS Class II–IV drugs’ in the biopharmaceutics classification system.